THE BACTERIUM Fusobacterium sp. MAY INTERFERE WITH CONCEPTION - & Saleh, Tawfeq (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was aimed to investigate microbiological and molecular markers of periodontal problems and its association with conception in 101 Iraqi women, 50 primary infertile while 27 secondary infertile and 24 pregnant as control group. Major periodontal pathogen in the subgingival plaque and cervical vaginal swab specimens was detected, and molecular marker (16SrRNA) gene used for detection of Fusobacterium in our study. Fusobacterium sp. isolates from oral samples were examined biochemically and confirmed by molecular detection, they were also subjected to antibiotic sensitivity test and were shown to be resistant to β-lactamase family of antibiotics and were mostly resistant to Ciprofloxacin. Four Fusobacterium sp samples were identified in both Oral samples and vaginal-cervical specimens of the same four women from the primary infertile group. Fusobacterium sp. was significantly (P<0.01) more frequently detected in the Oral samples and vaginal-cervical specimens among primary infertile group (38.7%) than pregnant (9.1%) as so among secondary (30.0%) than pregnant (9.1%). Analysis identified a model of a significant predictive factor of presence of Fusobacterium sp.: primary infertile [Odd ratio (OR) = 6.3 at 95% CI = 1.33-25.1] and secondary infertile OR = 4.2 at 95% CI = 1.84-12.22. this can show that infertalty state can be more risked than pregnant women to have the Fusobacterium sp and be effected by it.